Արևմտահայ գաղթականների վերադարձի հարցը (1898-1908 թթ.) - Քոսյան, Լիլիթ (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
In the 1890s, a large part of Western Armenians who survived the mass massacres organized by Abdul Hamid II took shelter in Eastern Armenia. They survived thanks to various aids. However, it was necessary to organize their return, first of all, to preserve the demographic picture in Western Armenia. Their process of returning to their homeland took place in two stages: in 1898 and in 1902. However, the actions showed that these speculations were made deliberately by Russia and the Ottoman Empire.
Keywords: Գաղթականություն; Պատմություն